Cover Image. Issue 3 (5th April 2020) - Matava, Clyde; Pankiv, Evelina; Ahumada, Luis; Weingarten, Benjamin; Simpao, Allan
Abstract : The cover image is based on the Original Article Artificial intelligence, machine learning and the pediatric airway by Clyde Matava, Allan F Simpao, Luis Ahumada et al., https://doi.org/10.1111/pan.13792 .